«Mas no de agua, de silencio corre este caudal»: el río San Juan de Nicaragua - Claire Pailler (Caravelle)
Many attempts have been made to follow the historical and mythical path of the San Juan River, spillway of Nicaragua’s lake: as a place where many national history war episodes have taken place, it has also sustained economical and political fantasies, and today, far from all kinds of rumours, it has become an essential reference of Nicaragua’s national identity.